Feeding habitat quality and behavioral trade-offs in chimpanzees: a case for species distribution models. (31st January 2016) - Foerster, Steffen; Zhong, Ying; Pintea, Lilian; Murray, Carson M.; Wilson, Michael L.; Mjungu, Deus C.; Pusey, Anne E.
Lay Summary: We introduce a new approach for modeling variation in feeding habitat quality on small spatial scales to aid the study of habitat selection and behavioral trade-offs. Our method combines predicted occurrences of food species, obtained using machine learning techniques, with their dietary importance. Applied to chimpanzee sightings at Gombe National Park, we find that females leave the best feeding areas to mate and that individuals who have resided in the community for longer generally occupy better feeding areas. Abstract: The distribution and abundance of food resources are among the most important factors that influence animal behavioral strategies. Yet, spatial variation in feeding habitat quality is often difficult to assess with traditional methods that rely on extrapolation from plot survey data or remote sensing. Here, we show that maximum entropy species distribution modeling can be used to successfully predict small-scale variation in the distribution of 24 important plant food species for chimpanzees at Gombe National Park, Tanzania. We combined model predictions with behavioral observations to quantify feeding habitat quality as the cumulative dietary proportion of the species predicted to occur in a given location. This measure exhibited considerable spatial heterogeneity with elevation and latitude, both within and across main habitat types. We used model results to assess individual variation in habitat selection among adult chimpanzees during a 10-year period, testing predictions about trade-offs between foraging and reproductive effort. We found that nonswollen females selected the highest-quality habitats compared with swollen females or males, in line with predictions based on their energetic needs. Swollen females appeared to compromise feeding in favor of mating opportunities, suggesting that females rather than males change their ranging patterns in search of mates. Males generally occupied feeding habitats of lower quality, which may exacerbate energetic challenges of aggression and territory defense. Finally, we documented an increase in feeding habitat quality with community residence time in both sexes during the dry season, suggesting an influence of familiarity on foraging decisions in a highly heterogeneous landscape.